The requirements for a dynamic bus crew scheduling system - Shibghatullah, Abdul Samad; Eldabi, Tillal; Rzevski, George (2006)
Bus crew scheduling problem is a complex problem because of the large number oi variables that are needed to be considered for Optimisation, such as complexity of allocating crew shifts; rising costs of crew; and unpredictability of traffic and crew availability. There is a number of existing scheduling systems that are able to produce optimal or near optimal schedules. However, to maintain such optimality in day-to—day operations. such scheduling systems need to extend their capabilities by enabling crew reassignment, a feature that is not currently available in most automated scheduling systems. This paper looks at the unpredictability problem more closely and investigates how bus companies currently manage their schedules. The information is elicited from literature and interviews from three bus companies in London,UK. Consequently, this paper proposes a set of requirements for a dynamic crew scheduling system that is able to perform crew reassignment in real time given the occurrence of unpredictable events such as lateness for duty, sick on duty, or crew absenteeism without prior notice. The proposed approach aims to dynamically maintain optimality throughout day~to~day operations.